Poetry in translation: traveling pleonasm and beyond - Lahiani, Raja (Penerbit Universiti Kebangsaan Malaysia, 2020)
Style is the kernel of literariness. This study examines the translatability of pleonasm, a form of redundancy considered a standard rhetorical device in Arabic but usually avoided in Western languages. The study evaluates and compares English and French translations of a pleonastic Arabic verse line. An acceptable translation of this verse should provide an affective-stylistic equivalent that will capture and convey the same appeal as the source text with a similar degree of literariness, not just a direct linguistic equivalent. This research asserts that a translator usually works within their own translation aesthetics, developed within their cultural and disciplinary traditions of literary and translational aesthetics and their idiosyncratic ideas about or interpretation of the source text.